METHOD OF PROCESSING THE WIND TURBINE TIME HISTORY LOADS BASED ON 6 DEGREES OF FREEDOM - LI JinKu; LIU Wei (Jixie qiangdu)
A method of simply wind turbine time history loads have been studied in the article,it can be converted the time history loads into some number of load duration distribution. It is based on the standard of ISO6336 by considering 6 degrees of freedom. The loads gotten by this method can be used to the designing loads of the wind gearbox by inputting it to the currently commercial gearbox designing software to calculated the system deformation. A comparison between the calculated loads spectrum and the torque spectrum provided by wind turbine factory have performed based on gear strength,the results presented slightly difference,but the calculating time decreased a lot. The method provided a preference to the wind gearbox manufacturer and other gearbox manufacturer process and program the design loads,and have some values of practical applications.